PENGELOLAAN SAMPAH RUMAH TANGGA BERBASIS 3R(REDUCE, REUSE, RECYCLE) - Kerlima Hutagaol; Khoirul Azhari Lubis; David Christian; Febbyan Akhfa Panca Andhika; Akhmad Faruq Muhamad Faisal (SINERGI : Jurnal Riset Ilmiah, 2026)
The waste management crisis in Jakarta's urban buffer zones, particularly South Tangerang City, reached a critical point due to the total overcapacity of the Cipeucang Final Disposal Site (TPA) in 2024, with waste generation exceeding 1,000 tons per day. This study aims to analyze the urgency of upstream waste management, evaluate the effectiveness of Reduce, Reuse, Recycle (3R) programs, and formulate an effective waste management model for the modern residential area of Bumi Serpong Damai (BSD). The research methodology employs a qualitative descriptive approach through a case study, relying on secondary data analysis (SIPSN reports, local/national regulations) and policy observation of waste processing (2024–2025). The results indicate that approximately 60–65% of waste in BSD originates from the domestic sector, dominated by inorganic packaging and organic food waste. Implementing 3R-based waste management at the cluster level through digital neighborhood-scale waste banks (serving 20–50 households) is proven to reduce residual waste volume sent to the landfill by 30–40%. The study concludes that the most effective model for an independent township is a dual-approach: integrating community-based sorting and recycling at the upstream level (social engineering & Waste Banks) with high-temperature Waste-to-Energy (WtE) or incinerator technology at the downstream level managed by Township Management